Students’ Creativity in Geometry Course : How a Mystery Box Game Plays Important Role - Wanda Nugroho Yanuarto (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2017)
The purpose of this study are encouraging students’ creativity by mystery box games and become more aware of their mathematical thinking. The situational problem as the starting point helps students to relate what they learn to problems in daily life, and construct and interpret geometry that are related to real situations, and this helps to correct their alternative conceptions in geometry courseto encourage students’ creativity in Geometry Course. There are three abilities to encouraging students’creativity, they are synthetic ability, analytic ability, and practical ability. The subjects of this research is the students of the 1st semester of 2014 academic year class A of mathematical education of Muhammadiyah University of Purwokerto, Central Java, Indonesia. The data of this research is through observation sheet, recording videos, portofolios, and questionnaires. Those data was analyzed through data reduction, data presentation, and conclusion. This study shows that to encouraging students’ creativity can analyzed by mystery box in Geometry Course.